Assessing the effect of walnut (juglans regia) and olive (olea europaea) oil against the bacterial strains found in Gut Microbiome - Zahid, Hena; Shahab, Mohsin; Ur Rahman, Shafiq; Iqbal, Zafar; Khan, Ayaz Ali; Aziz, Tariq; Ali, Waqar; Zamani, Ghazala Yasmin; Ahmad, Saeed; Shahzad, Muhammad; Alharbi, Metab; Alshammari , Abdulrahman (Progress in Nutrition, 2022)
The problem of drug-resistance developed by bacteria against antibiotics turned the attention of researchers to find out and develop such products which haven’t such issues. For this purpose, this study was carried out by using walnut and olive oil against several gram negative and gram-positive bacteria. Different concentrations of oils were employed using disc diffusion method. They exhibited better antibacterial properties. All the tested bacteria, viz. Citrobacter freundii, Enterobacter aerogenes, Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella typhi, Salmonella typhimurium, and Shigella sonnei were considered susceptible to certain concentrations of both walnut and olive oil. High bacterial activity (18.9±0.7 mm) of walnut oil was observed against Salmonella typhi, 17±1.2 mm against Proteus vulgaris, 16.90±1.5 mm against Citrobacter freundii, 15±0.8 mm against Pseudomonas aeruginosa, and 14±1.3 mm against Klebsiella pneumoniae, while average activity was 13±1.2 mm against Salmonella typhimurium, 12.90±1.5 mm against Enterobacter aerogenes, 12±1.5 mm against Escherichia coli and 12±1.00 mm against Shigella sonnei. Similarly, olive oil had its maximum antibacterial activity 26±1.5 mm, 23.1±1.00 mm, 19±1.5 mm, 19±1.5 mm, 19±0.8 mm, 18±1.1 mm, 18±1.5 mm, 15±1.00 mm, 15±0.7 mm, 14±1.1 mm against Enterobacter aerogenes, Salmonella typhi, Citrobacter freundii, Escherichia coli, Shigella sonnei, Klebsiella pneumoniae, Proteus vulgaris and Pseudomonas aeruginosa, respectively, whereas, optimum activity of olive oil was recorded against Salmonella typhimurium (13.15±1.0 mm). These findings showed that walnut and olive oils have a substantial effect on bacteria and can be used as effective antibacterial agents in the development of medicines.